A Review of Nesting Behavior in the Genus Entomognathus, With Notes on E. Memorialis Banks (Hymenoptera: Sphecidae) - Richard C. Miller; Frank E. Kurczewski (Psyche: A Journal of Entomology)
The genus Entomognathus contains at least 4o species, half in the Ethiopian and in the Palaearctic, Nearctic, Oriental, and Neotropical regions (Leclercq, 1954, 1955, 1961, 1963; Nouvel and Ribaut, 1956; Krombein, 1963). Relatively little is known about the nesting behaviors, host preferences, or life histories of members of this genus. Only the Palaearctic E. (Entomognathus) brevis van der Linden has been studied in any detail, and almost nothing is known about the four U. S. species belonging to the subgenus Toncahua One of the purposes of the present paper is, therefore, to amalgamate information on the host preferences, nesting behaviors, life histories, and immature stages of the species of Entomognathus, based upon a review of the world literature. The major portion of this paper details the components of the nesting behavior of E. (Toncahua) memorialis Banks, describes the mature larva and cocoon, and compares this species and related crabronine and larrine wasps in nesting ethology and larval and cocoon morphology. The adult wasps and prey beetles have been placed in the S. U. N. Y. College of Forestry Insect Museum. and the mature larva has been deposited in the Museum of Comparative Zoology, Harvard University.